Effect of Low Molecular Weight Heparin, Dextran and Their Combinations on Experimental Venous Thrombosis in Rabbits - Matthiasson, Stefan E; Lindblad, Bengt; Mätzsch, Thomas; Holst, Jan; Bergqvist, David (Thrombosis and Haemostasis, 1994)
An experimental model based on the combination of endothelial damage and flow reduction was used to induce jugular vein thrombosis in rabbits. The effect on thrombosis of a low molecular weight heparin (LMWH [Fragmin]), dextran 70, placebo and their combination was studied in a double-blind fashion with actual doses used in clinical thromboprophylaxis. Saline and polygeline were used as placebo in the control group. Four groups with 120 isolated vein segments in 60 animals were studied for presence of thrombus formation, occlusive thrombi and thrombus weights. Dextran reduced the thrombus weights (p = 0.048) and the formation of occlusive thrombi (p = 0.01), but not the formation of thrombi when compared with the placebo control group. Similarily, LMWH reduced the thrombus weights (p = 0.046), the formation of thrombi (p = 0.007) and occlusive thrombi (p = 0.0001). Compared with the LMWH group the group treated with the combination of LMWH and dextran was found to reduce the frequency of occlusive thrombi (p = 0.03) and numerically, but not significantly, further reduce the overall frequency of thrombosis (p = 0.18) and thrombus weights (p = 0.11). The results are consistent with an augmentation of the antithrombotic effect of LMWH by dextran 70. The need for further evaluation of the combined efficacy of LMWH and dextran is apparent from this study.